Design of encrypted transceiver Non-coherent OFDM with ability to correct coding bits of information - Kareem J. Thajeel; Izz K. Abboud; Laith A. Kunbar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A differential encrypted transceiver was designed in the signal-to-noise ratio systems. A time"-"spread" frequency-"encoded (TSFE) algorithm was proposed using the orthogonal frequency multiplexing multiplier OFDM. The proposed design was verified under the Doppler frequency effect and there was an improvement in the performance of the signal-to-noise ratio system. As a result, the reliability of decoded data was increased and achieves the ability to correct coding bits of information.